2017
DOI: 10.1016/j.ymthe.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Gene Therapy Counteracts the Development of Non-ischemic Cardiomyopathy in Mice

Abstract: A causal role of hypercholesterolemia in non-ischemic heart failure has never been demonstrated. Adeno-associated viral serotype 8 (AAV8)-low-density lipoprotein receptor (AAV8-LDLr) gene transfer was performed in LDLr-deficient mice without and with pressure overload induced by transverse aortic constriction (TAC). AAV8-LDLr gene therapy resulted in an 82.8% (p < 0.0001) reduction of plasma cholesterol compared with controls. Mortality rate was lower (p < 0.05) in AAV8-LDLr TAC mice compared with control TAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Plasma cholesterol and lipoprotein cholesterol levels were determined using a Cholesterol Quantification kit from Sigma-Aldrich (Sigma, St. Louis, MO, USA). HDL and non-HDL lipoproteins were separated by ultracentrifugation as described [69]. Plasma triglyceride concentration was quantified using the Triglyceride Quantification kit MAK266 (Sigma, St. Louis, MO, USA) according to the instructions of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma cholesterol and lipoprotein cholesterol levels were determined using a Cholesterol Quantification kit from Sigma-Aldrich (Sigma, St. Louis, MO, USA). HDL and non-HDL lipoproteins were separated by ultracentrifugation as described [69]. Plasma triglyceride concentration was quantified using the Triglyceride Quantification kit MAK266 (Sigma, St. Louis, MO, USA) according to the instructions of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma cholesterol levels were determined using a Cholesterol Quantification kit from Sigma (Sigma, St. Louis, MO, USA). HDL and non‐HDL lipoproteins were separated by ultracentrifugation as described previously (Muthuramu et al, ). Triglyceride concentration was determined in plasma using the Triglyceride Quantification kit MAK266 (Sigma‐Aldrich, Schnelldorf, Germany) according to the instructions of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that intervention with MDCO-216 reverses established pathological remodeling induced by pressure overload and constitutes a successful treatment for heart failure in mice with pressure overload [ 23 ]. Since pressure overload induced by transverse aortic constriction (TAC) leads to cardiac dilatation and HFrEF [ 24 ], the question remains whether this HDL-targeted intervention may be effective in HFpEF.…”
Section: Introductionmentioning
confidence: 99%